2001
DOI: 10.1385/ep:12:2:181
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of p27 (Kip1) in Human Pituitary Glands and in Various Types of Pituitary Adenomas

Abstract: p27 (Kip1) plays regulatory roles in the cell cycle by inhibiting the activity of cyclin dependent kinases (CDKs). This immunohistochemical study is aimed at elucidating the expression of p27 in human pituitary and in various types of pituitary adenomas in order to clarify its role in the regulation of proliferation. Sixteen normal pituitary glands and 179 human pituitary adenomas were used for immunohistochemical studies. The tissues were fixed in 10% formalin and embedded in paraffin. Indirect peroxidase met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Furthermore, we found levels of MEN1 and p27 mRNAs to be low in the recurrent prolactinoma. Although most of previous studies reported low expression of p27 in the sporadic pituitary adenomas, expression levels of menin and MEN1 mRNA have been inconsistent [20][21][22][23][24][25][26][27]. The discrepancy between our data and previous reports may be due to the different antibody used for immunocytochemistry or the method for real-time PCR; we used TaqMan probes and others used regular RT-PCR and semiquantitative analysis.…”
Section: Acknowledgmentcontrasting
confidence: 81%
“…Furthermore, we found levels of MEN1 and p27 mRNAs to be low in the recurrent prolactinoma. Although most of previous studies reported low expression of p27 in the sporadic pituitary adenomas, expression levels of menin and MEN1 mRNA have been inconsistent [20][21][22][23][24][25][26][27]. The discrepancy between our data and previous reports may be due to the different antibody used for immunocytochemistry or the method for real-time PCR; we used TaqMan probes and others used regular RT-PCR and semiquantitative analysis.…”
Section: Acknowledgmentcontrasting
confidence: 81%
“…Overexpression of p27 leads to cell-cycle arrest (7), while lack of p27 results in pituitary adenomas in p27 'knockout' animals (8)(9)(10). We, and others, have previously shown reduced expression of p27 in a variety of pituitary adenomas (11)(12)(13)(14)(15), although a single study was not able to confirm this (16).…”
Section: Introductionmentioning
confidence: 87%
“…Disruption of p27, which is a member of the CIP1/KIP1 family, in mice resulted in tumors of the pituitary intermediate lobe and multi-organ hyperplasia [24,38]. Interestingly, immunohistochemical study of human pituitary adenomas showed that the level of p27 expression in ACTHoma was markedly lower compared with other types of pituitary adenomas [26]. These findings suggest the intermediate lobe specific role of p27.…”
Section: Cell Cycle Regulatorsmentioning
confidence: 95%